(untitled) (Journal of Nuclear Technology in Applied Science, 2019)
The ethanol, methyl alcohol and acetone (80%) extracts of gamma-irradiated red beet leaves and roots (at dose levels of 0, 3, 6, 9 and 12 kGy) were made to be used as a natural antioxidant and antibacterial agents. The total phenolic contents (TPC) and total flavonoid contents (TFC) were estimated in the leave and root extracts. The antioxidant activity was determined by DPPH and FRAP methods. Antibacterial activity was carried out against S. aureus, B. cereus, E. coli and S. typhimurium. The obtained results indicated that the ethanol extracts had higher total phenolics, fl avonoids content and antioxidant activity in both leaves and roots than other solvents extract after solid-phase extraction. The results showed that 9 kGy doses significantly increased the TPC, TFC and enhanced the antioxidant activity of leaves and roots. The majority trend in obtaining data summarized that both non-irradiated and irradiated red beet roots (RBR) extracts possess higher antibacterial activity against selected bacteria than red beet leaves (RBL) extracts. Last, the obtained data showed that red beet is a very bright source of bioactive compounds and it is a very potent natural source of antioxidant compounds.